Product Quality Regulation and New Drug Introductions: Some New Evidence from the 1970s - Wiggins, Steven N. (The Review of Economics and Statistics, 1981)
Villani, Samuel Wagner, and Frank Husic, The Prohctiontiii d Application of'Ne(it Industrial Technology (New York: W. W. Norton, 1977). Mansfield, Edwin, Anthony Romeo, Mark Schwartz, David Teece, Samuel Wagner, and Peter Brach, Technology Tr naiis fel, Productivity, aind Economic Policy (New York: W. W. Norton, forthcoming). National Science Foundation, Methodology of Statistics on Research a1nzd Development (Washington, D.C.: Government Printing Office, 1959). Resarchili(hid D)evelopment in Idiidstry, 1974 (Washington, D.C.: Government Printing Office, 1976). Scherer, F. M., Industrial Market Structure antd Economic Pe orrniance, 2nd ed. (Chicago: Rand McNally, 1980). Shepherd, William, The Ecoiomics of Industl-ial Orgonizlation (Englewood Cliffs: Prentice-Hall, 1979). Teece, David, and Henry Armour, Innovation and Divestiture in the U.S. Oil Industry,' in D. Teece (ed.), R (ind D in Eniergv (Stanford: Stanford University, 1977).